European UV DataBase (EUVDB) as a repository and quality analyser for solar spectral UV irradiance monitored in Sodankylä - Heikkilä, Anu; Kaurola, Jussi; Lakkala, Kaisa; Karhu, Juha Matti; Kyrö, Esko; Koskela, Tapani; Engelsen, Ola; Slaper, Harry; Seckmeyer, Gunther (Geoscientific Instrumentation, Methods and Data Systems, 2018)
Databases gathering atmospheric data have great potential not only as data storages but also in serving as platforms for coherent quality assurance (QA). We report on the flagging system and QA tools designed for and implemented in the European UV DataBase (EUVDB; http://uv.fmi.fi/uvdb/ ) for measured data on solar spectral UV irradiance. We confine the study on the data measured by Brewer #037 MkII spectroradiometer in Sodankylä (67.37° N, 26.63° E) in 1990–2014. The quality indicators associated with the UV irradiance spectra uploaded into the database are retrieved from the database and subjected to a statistical analysis. The study demonstrates the performance of the QA tools of the EUVDB. In addition, it yields an overall view of the availability and quality of the solar UV spectra recorded in Sodankylä over a quarter of a century. Over 90 % of the four main quality indicators are flagged as GREEN, indicating the highest achievable quality. For the BLACK flags, denoting data not meeting the pre-defined requirements, the percentages for all the indicators remain below 0.12 %.